PENCIPTAAN KARYA SENI INSTALASI BERBASIS EKSPERIMEN KREATIF DENGAN MEDIUM GEMBRENG - Cholis, Henri (Institut Seni Indoensia Surakarta, 2015)
This research is a study on an installation work of art based on an experimentation exploring newÂ possibilities of the product of gembreng (zinc) handicrafts in Kabangan market, Laweyan, Surakarta.Â The product is used as one of the aesthetic elements of the installation art in a ready made shape or anew one which can be developed using a technique craftsmen in Kabangan market have. This researchÂ aims at studying to create an installation work of art with zinc as the main medium. This research isÂ designed as an explorative developing research. Therefore, it tends to be experimentative to findÂ possible innovation in shape, technique, medium, and material exploration. The data were collectedÂ through in-depth interview and an observation in the zinc industrial centre in Kabangan market,Â Laweyan, Surakarta. The subjects of this research were the craftmen of zinc to find out the techniqueÂ they usually used and the technical achievement which could be explored to create an installationwork of art. The object observed in this research was the product produced and the technique used toÂ create the handicraft in Kabangan market. It is important to do this to find out various possibilities ofÂ developing shapes as an aesthetic element of an installation work of art.To enhance the validity andquality of the work of art in this research, â€œtrial and seeâ€ or the controlled trying out by an adaptiveÂ strategy is used. The data were analyzed using SWOT analysis and the result of the analysis was usedÂ as the principle to make an installation work of art. The idea of shape in this installation work of artis based on Garuda and Jatayu, a kind of birds thought to be sacred in Javanese myth. The stages inÂ creating this work of fine art are as follows: exploration, improvisation, and shaping. The result ofÂ this research is an installation work of art of which the main material is zinc and its shape, colourÂ and ornament originate in Javanese culture.Keywords: Javanese myth, handicraft made of zinc, installation work of art.